Assistance for Independent Workers in Strengthening Business Proposals and Strengthening Business Financial Recording for Business Development - Luluk Tri Harinie; Lelo Sintani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of mentoring activities in the community is to empower independent workers through capacity building in strengthening business proposals and strengthening business financial records. The implementation of the activity in Baun Bango Village, Kamipang District, Katingan Regency, Central Kalimantan Province involved as many as 20 (twenty) members who were representatives of 10 (ten) pond fishery groups that were activity partners. The method of implementing activities is carried out using counseling, training, and direct practice methods for assisting in strengthening business proposals and assisting in strengthening financial records. As a result of community assistance activities for independent workers, activity partners are able to develop pond fishing businesses.